THE INFLUENCE OF LEADERSHIP STYLE MANAGEMENT AND COMPENSATION ON PERFORMANCE FOR CONTRACT EMPLOYEES AT LEMBANG HOSPITAL - Hidayat, Muhammad; Diana Pratiwi, Teggy Diana Pratiwi2; Ratnajaya, Aep; Shintya Dewi, Maria; Karlina, Nova; Sikki, Nurhaeni (JURNAL EKBIS, 2024)
The purpose of this research is to determine the influence of leadership style management and compensation on performance for contract employees at Lembang Regional Hospital. A quantitative approach was used in this research with 207 employees as respondents. This journal discusses an introduction consisting of problem background, problem formulation, objectives and theoretical review. Another aim of this journal is to answer the hypothesis proposed in this research. Data was collected using questionnaires and quantitative analysis which was processed using SPSS. The results obtained in this research are that leadership style and compensation have a significant influence on the performance of contract employees at Lembang Regional Hospital.